Factors affecting blood parameters of autochthonous Cika cattle - Klinkon, Martina; Simčič, Mojca; Ježek, JozÌŒica; Klinkon, Zoran; Kompan, Dragomir (Acta Agraria Kaposváriensis, 2010)
Cika cattle is the only Slovenian autochthonous cattle breed, which has been preserved to the present days. The aim of this study was to determine the blood parameters of Cika cattle regarding the variability in phenotypes and age of Cika cattle. This study included 122 Cika cattle of two phenotypes (71 Cika and 51 Pinzgauer phenotypes) from different farms and regions of Slovenia. There were 108 cows and 14 sires for natural mating. The average age of sires at sampling were 2.0 years, the average age of cows at sampling was 8.6 years. Farms with Cika cattle were placed from 200 m to 1100 m above the sea level with an average altitude of 643.5 m. The number of erythrocytes (RBC), leucocytes (WBC) and platelets (PLT) and values of haemoglobin (Hb), haematocrit (Ht), the mean corpuscular haemoglobin (MCH) and the mean corpuscular haemoglobin concentration (MCHC) were measured with haematological analyser ABC Vet. Data were analysed by GLM procedure of statistical package SAS/STAT considering phenotype and sex as fixed effects as well as animal age as linear regression. Analysis of variance proved that the sex significantly affected almost all included blood parameters of Cika cattle except MCHC. The effect of age at the day of blood collecting affected the RBC, WBC, values of Hb and Ht, while the effect of phenotype affected only the MCHC.
Keywords: cattle; Cika; autochthonous breed; blood parameters